Comparing psoriatic arthritis low-field magnetic resonance imaging, ultrasound and clinical outcomes: data from the TICOPA trial - Helliwell, P; Coates, L; Chew, N; Lettieri, G; Moverley, A; Freeston, J; Nam, J; Waxman, R; Emery, P; Conaghan, P (Journal of Rheumatology, 2019)
Objective. The Tight Control of inflammation in Psoriatic arthritis (TICOPA; isrctn.com: ISRCTN30147736) trial compared standard care (StdC) and tight control (TC) in early psoriatic arthritis (PsA), demonstrating better outcomes for TC. This substudy evaluated the performance metrics of modern imaging outcomes and compared them to the clinical data.